2014
DOI: 10.15666/aeer/1203_661679
|View full text |Cite
|
Sign up to set email alerts
|

The impact of human land use on the composition and richness of ground and dung beetle assemblages

Abstract: Plexida et al. : The impact of human land use on the composition and richness of ground and dung beetle assemblages - Abstract. This paper presents the results of a survey on the habitat and seasonal variation in activity density and richness of ground and dung beetle assemblages in a heterogeneous landscape of central Greece. Beetles were collected using 2,646 pitfall traps across an area of 138 ha representative of the Mediterranean mountainous landscape. Sampling was performed in cereal fields, corn fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Forestry plantations frequently have a negative effect on vertebrate diversity (Barlow et al ., 2007a), including amphibians (Kudavidanage et al ., 2012), birds (Castaño‐Villa et al ., 2019), and mammals (Begotti et al ., 2018), or invertebrates, such as coleopterans (Horák et al ., 2019; Méndez‐Rojas et al ., 2021) or butterflies (Kudavidanage et al ., 2012). However, other studies found biodiversity levels within plantations to match those found in natural forests, particularly in non‐tropical biomes (Plexida et al ., 2014; Magura et al ., 2015). A global understanding of the relative merits of forestry plantations as biodiversity supporters thus remains a core question.…”
Section: Introductionmentioning
confidence: 99%
“…Forestry plantations frequently have a negative effect on vertebrate diversity (Barlow et al ., 2007a), including amphibians (Kudavidanage et al ., 2012), birds (Castaño‐Villa et al ., 2019), and mammals (Begotti et al ., 2018), or invertebrates, such as coleopterans (Horák et al ., 2019; Méndez‐Rojas et al ., 2021) or butterflies (Kudavidanage et al ., 2012). However, other studies found biodiversity levels within plantations to match those found in natural forests, particularly in non‐tropical biomes (Plexida et al ., 2014; Magura et al ., 2015). A global understanding of the relative merits of forestry plantations as biodiversity supporters thus remains a core question.…”
Section: Introductionmentioning
confidence: 99%
“…Land cover change research has an important role in understanding the intensity and dynamics of real global processes [3][4][5][6][7]. The Land-Cover and Land-Use Change (LCLUC) Program launched by the National Aeronautics and Space Administration (NASA) is studying natural and human-induced changes of the vegetation of the Earth and consequences of environment transformation processes and attempts to forecast natural disasters considering the Earth as a single complete system, with the help of satellite images, using the tools of NASA and combining them with laboratory and modeling work [8].…”
Section: Introductionmentioning
confidence: 99%
“…Also impor- However, many new theoretical trends have emerged recently [14,15], a number of new methods are used [16], and biogeography has gained outstanding social significance through the effects of human land use on natural communities [17]. …”
mentioning
confidence: 99%